DMAIC Method of Quality Improvement of Ground Works Processes: Case Study. (January 2019) - Nowotarski, Piotr; Szymanski, Pawel; Rzepecka, Patrycja
Abstract: The foundations are important part of every building's structure. It can be distinguished square foundations and deep foundations. The process of creating foundations during building construction can be in some cases very complicated and, similar to other construction processes, very costly when errors and problems occurs. Lean construction is a management strategy to eliminate possible errors and wastes during execution of the processes, which is why it is nowadays more widely used for prevention, as well as in the situation of emergency, when solutions already prepared are executed according to the plan. One of the methods that can help in successful implementation of good practices in construction from the quality management perspective is DMAIC, which means Define-Measure-Analyze-Improve-Control. Authors decided to use it for the purpose of this publication. Article presents the use of the DMAIC concept on the example of foundation preparation in the construction site in the city of Koło. The paper presents methods of quality management in the construction process based on foundation works. The quality analysis was based on the DMAIC method, in which the following quality analysis methods were used: Ishikawa diagram, FMEA analysis, Pareto chart. The proposed methods and solutions can be implemented on other construction sites conducting similar processes. Attention is drawn to the need for further research to be carried out to confirm the estimated values of solving problems ratio in groundworks processes, which authors are planning to execute on similar construction site in Poznań.